Analisis Kapasitas Ruang Parkir di Fakultas Teknik Universitas Cenderawasih - Kanz Maulana Tsany Mayabubun; Monita Yessy Beatrick Wambrauw; Marsal Arung Lamba (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
To meet the needs of safety and comfort within the Faculty of Engineering, Cenderawasih University, the campus has provided a fairly adequate parking area. With the parking area that is already available, it is necessary to conduct an analysis of the need for parking areas within the Faculty of Engineering, in order to arrange vehicles that are neater, safer and more comfortable. The formulation of this research problem is in the form of existing parking conditions, parking characteristics, and ideal parking lot capacity. This research aims to identify problems, analyze characteristics, and determine the size of Parking Lot Units. The benefits of research for reference materials, input to local governments related to parking solutions. Make a calculation of the parking lot capacity. The limitations of the research problem, which was carried out in the parking lot of the Faculty of Engineering, Cenderawasih University and the number of parking lot capacity, Calculating the capacity of the type of motorcycle and car vehicles, the survey was carried out on 3 (three) active working days, namely Monday. Wednesday, and Friday for 3 (three) weeks. This research method uses a quantitative approach with a survey type of research. With this research, it is hoped that the Faculty of Engineering, Cenderawasih University can provide adequate parking lots.